Assessment of the quality of randomized controlled trials in surgery using Jadad score: Where do we stand? - Mohsina, S; Gurushankari, B; Niranjan, R; Sureshkumar, S; Sreenath, GS; Kate, V (Journal of postgraduate medicine, 2022)
Introduction: Quality assessment of randomized controlled trials (RCTs) is important to prevent clinical application of erroneous results. Materials and Methods: This was an assessment of published RCTs in surgical subspecialties during 2011-2018 based on MEDLINE and EMBASE search. The primary objective of the present study was to quantitatively and qualitatively analyze the RCTs published from India based on year of publication, geographical distribution, and subspecialty using the modified Jadad score (high quality if score is ≥3; or ≥2 if blinded design was not feasible). Its secondary objective was to identify factors affecting the quality of RCTs. Results: Among 1304 trials identified, 162 were analyzed. Of these 96 (59%) had a score of ≥3; and 104 (64.2%) were of high quality (score ≥2). Year-wise there was no significant quantitative (P = 0.329) or qualitative (P = 0.255) variation. Geographic regions had similar quantity (P = 0.206) and quality (P = 0.068). The RCTs among subspecialties too were comparable in quantity and quality. Higher impact factor of journal (P = 0.013) and assessment by Institute Review Board (IRB) (P = 0.004) were significantly associated with a better study quality. Type of institution, number of authors, centricity, assistance by a statistician, and source of funding did not affect the quality of RCTs. Conclusions: The quantity and quality of surgical RCTs were stable and comparable over the years and across geographical regions and subspecialties. Higher impact factor of journal and review by IRB were significantly associated with a better study quality.